# -8y+9=-9y+6

## Simple and best practice solution for -8y+9=-9y+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -8y+9=-9y+6 equation:

Simplifying
-8y + 9 = -9y + 6
Reorder the terms:
9 + -8y = -9y + 6
Reorder the terms:
9 + -8y = 6 + -9y
Solving
9 + -8y = 6 + -9y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '9y' to each side of the equation.
9 + -8y + 9y = 6 + -9y + 9y
Combine like terms: -8y + 9y = 1y
9 + 1y = 6 + -9y + 9y
Combine like terms: -9y + 9y = 0
9 + 1y = 6 + 0
9 + 1y = 6
Add '-9' to each side of the equation.
9 + -9 + 1y = 6 + -9
Combine like terms: 9 + -9 = 0
0 + 1y = 6 + -9
1y = 6 + -9
Combine like terms: 6 + -9 = -3
1y = -3
Divide each side by '1'.
y = -3
Simplifying
y = -3`